2012
DOI: 10.1007/s10654-012-9654-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal asthma on perinatal outcomes: a two-stage sampling cohort study

Abstract: There are conflicting results concerning the impact of maternal asthma during pregnancy on perinatal outcomes. The present study investigated the associations between maternal asthma during pregnancy and the risk of a small-for-gestational-age (SGA) infant, a low-birth-weight (LBW) infant, and preterm birth. A population-based cohort of 40,788 pregnancies from asthmatic and non-asthmatic women was reconstructed through the linking of three Quebec (Canada) administrative databases between 1990 and 2002. A two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…However, the effect of asthma during pregnancy on BW is poorly characterized. Although some studies found no association between maternal asthma and BW (25), others reported lower BW in infants born to asthmatic women (26). Severe exacerbations of asthma or moderate to severe asthma during pregnancy have been shown to increase the risk of LBW (29), while maternal forced expiratory volume in one second is directly positively associated with BW (23).…”
Section: Discussionmentioning
confidence: 97%
“…However, the effect of asthma during pregnancy on BW is poorly characterized. Although some studies found no association between maternal asthma and BW (25), others reported lower BW in infants born to asthmatic women (26). Severe exacerbations of asthma or moderate to severe asthma during pregnancy have been shown to increase the risk of LBW (29), while maternal forced expiratory volume in one second is directly positively associated with BW (23).…”
Section: Discussionmentioning
confidence: 97%
“…It is also possible that preterm birth and asthma share common genetic determinants or environmental exposures. For instance, studies have indicated that maternal asthma is associated with both preterm birth and childhood asthma [9,52]. …”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results regarding the impact of asthma on pregnancy . Studies indicate association of disease with low APGAR score and or intrauterine growth restricted newborns in addition to prematurity, especially related to the severity of the disease [19]. However, in meta-analysis performed by Murphy et al, no increased risk was verified for the adverse events [20].…”
Section: Discussionmentioning
confidence: 97%